Understanding The Current Knowledge and Potential Research of Indonesia’s Only Protected Amphibian: The Bleeding Toad (Leptophryne cruentata) - Tohir, Rizki Kurnia; Kusrini, Mirza Dikari; Mardiastuti, Ani; Rahman, Dede Aulia (Journal of Tropical Biodiversity and Biotechnology, 2025)
Globally, amphibian populations are facing a substantial decline attributed to environmental degradation and lack of public attention. Indonesia, which one of countries with the high number of amphibian species in the world, paradoxically holds the record for the highest number of data-deficient amphibians. Indonesia currently has only one protected species, the bleeding toad (Leptophryne cruentata) also categorized as Critically Endangered. Considering this, our study undertakes a comprehensive review of bleeding toad research, highlighting research gaps and identifying potential topics for future investigations. In this study, we used an electronic database to acquire relevant studies aligned with our research objectives. The literature collection process involved the utilisation of the Publish or Perish (PoP) and manual internet searches. Our documentation reveals limited literature on bleeding toads, comprising only 20 reviews, with a notable prevalence of grey literature. This underscores the critical endangerment of bleeding toads, coupled with their neglect in research endeavours. Furthermore, our examination presents limited information on crucial aspects, such as taxonomy, morphology, geographical distribution, habitat characteristics, encounter records, behaviour, protection status, threats, and bioprospecting. The research gap is exceptionally high, with only two out of the 11 research topics attaining sufficient research status. Our findings underscore the urgent need for further research in this area. We identified at least 18 potential research areas that were essential for completing the baseline data. These findings serve as a valuable resource for researchers and policymakers seeking to address the critical endangerment of bleeding toads and to formulate effective conservation strategies.